Binge Drinking and Drug Use Among College Students: A Test of Hirschi's Social Control Theory - Riley-Cook, Katelyn (2012)
This thesis tests Travis Hirschi's Social Control Theory using a sample of college students. The purpose of the study was to examine whether social bonds (attachment, commitment, involvement, and belief) impact binge drinking and drug use among college students. In addition, this study assessed the need for drug and alcohol intervention and prevention measures. Random classes were selected from a college catalogue, and a total of five classes were surveyed. The total sample size was 193 students from a Bay Area university. The research revealed little support for Hirschi's theory. Contrary to the theory, the research showed that attachment to peers increased the likelihood of student binge drinking and drug use. Specifically, students who respected their best friend's opinions about the important things in life were more likely to binge drink, while students who wanted to be more like their friends were more likely to use drugs. However, consistent with Hirschi's assertion, believing it is okay to get around the law if one can get away with it increased the likelihood that a student used drugs, and respect for police decreased the likelihood that a student used drugs